The dilemma of restorative justice in the new criminal code: Opportunities for rehabilitation and the threat of normative uncertainty - Endro Nurwantoko (Institute Of computer Science (IOCS), 2026)
This study analyzes the regulatory space for restorative justice within the new Criminal Code (KUHP) and its implications for legal certainty, sentencing effectiveness, and social acceptance. Employing a normative juridical method, the research relies on statutory, conceptual, and analytical approaches and uses document analysis of the KUHP and related legal instruments as secondary legal materials. The study specifically examines the general principles stipulated in Articles 2 and 3, the alternative sentencing provisions in Articles 52 to 54, and the regulation of minor offenses in Articles 234 and 235 to systematically assess the normative design, coherence, and operational feasibility of restorative justice mechanisms. Previous research has largely focused on the conceptual justification or policy discourse of restorative justice without systematically examining the specific normative structure and internal coherence of restorative provisions within the new KUHP. The findings show that although the new KUHP provides a philosophical and normative foundation for implementing a restorative approach, the existing legal formulations still contain normative gaps, unclear criteria, and potential ambiguities that may trigger disparities in law enforcement. The analysis also reveals sociocultural barriers, including the strong retributive paradigm prevalent among both the public and law enforcement officers. These findings affirm that the success of restorative justice requires more detailed implementing guidelines, harmonization with other regulations, and the strengthening of a legal culture that supports restoration. Thus, while the new KUHP holds the potential to promote a more humanistic penal reform, it requires regulatory and institutional refinement to ensure consistent and effective implementation.